THE EFFECT OF PRODUCT QUALITY, LIFESTYLE, ISLAMIC BRANDING, AND ISLAMIC ADVERTISING ETHICS ON THE PURCHASE DESICION FOR BUTTONSCARVES - Zulkhaira, Salwa; Sitepu, Novi Indriyani (Universitas Syiah Kuala, 2024)
This study aims to examine how product quality, lifestyle, Islamic branding, and Islamic advertising ethics impact the purchase decisionofButtonscarvesproducts in Banda Aceh City. It adopts a quantitative approach, gathering primary data through questionnaires distributed to 165 respondents. Respondents were selected using purposive sampling with the Hair method. Data were analyzed using multiple linearregression. The findings indicate that individually, product quality, lifestyle, Islamic branding, and Islamic advertising ethics positively and significantlyinfluence the purchase decisionforButtonscarvesproducts. Simultaneously, these variables collectively demonstrate a positive and significant impact onpurchasedecisionforButtonscarvesproducts.